Epidemiological characteristics of acute viral and mycoplasma respiratory infections in Yongzhou, China: a retrospective descriptive study - Ying Jiang; Ying Jiang; Junyan Lu; Junyan Lu; Zhengrong Tan; Zhengrong Tan; Hanmei Wan; Hanmei Wan; Min Tang; Min Tang; Jiani Li; Jiani Li; et al. (Frontiers in Public Health)
BackgroundAcute respiratory infections (ARIs) are major global public health concerns. Understanding the epidemiological characteristics and evolution patterns of respiratory pathogens before and after the coronavirus disease 2019 (COVID-19) pandemic is crucial for disease control and prevention. This study identified the epidemiological characteristics and pathogen distribution in hospitalized patients with ARIs in Yongzhou, China.MethodsA retrospective analysis was conducted on 10,728 hospitalized patients with ARIs at a tertiary hospital in Yongzhou, China, from January 2019 to June 2024. Respiratory specimens were tested using standardized protocols including multiplex real-time PCR for detecting common respiratory pathogens (FluA and FluB, RSV, ADV, HRV, and MP) and next-generation sequencing for additional pathogen identification when clinically indicated. Statistical analyses included descriptive statistics for demographic and clinical characteristics, and chi-square tests for comparing categorical variables across different age groups, seasons, and time periods.ResultsOverall, 43.12% (4,626/10,728) of samples were positive for at least one pathogen. The most frequently detected pathogens were FluA (11.95%), RSV (9.61%), and MP (8.73%). RSV primarily affected children under 5 years (38.63% of RSV cases), while SARS-CoV-2 showed higher detection rates in older adult populations (64.81% of COVID-19 cases). Co-infections were found in 23.76% (1,099/4,626) of positive samples, with preschool children (2–5 years) showing the highest rate at 32.58%. MP (n = 398, 36.21% of all co-infections) with HRV (n = 338, 30.76% of all co-infections) were the most frequently detected pathogens in co-infections. Significant seasonal variations were observed, with winter showing the highest pathogen detection rates (49.04%, p < 0.001), and seasonal patterns changed notably during the COVID-19 pandemic. The frequency and patterns of co-infections showed marked differences across pre-pandemic, pandemic, and post-pandemic (January 2023–June 2024) periods. Co-infections occurred in 1,209 cases, with significant differences across study periods: 20.6% in pre-pandemic, 0.6% during pandemic, and 78.8% in post-pandemic periods (p < 0.001).ConclusionThis study revealed distinct age-dependent and seasonal distribution patterns of respiratory pathogens in Yongzhou, China. The significant changes in pathogen circulation dynamics before, during, and after the COVID-19 pandemic highlight the importance of continuous surveillance of respiratory viruses. These findings provide valuable insights for optimizing local ARI prevention and treatment services.